THE ROLE OF QUALITATIVE CHARACTERISTICS OF ACCOUNTING INFORMATION ON THE INVESTMENT EFFICIENCY AT MANUFACTURING COMPANIES IN INDONESIA - Oktorina, Megawati; Rajagukguk, Lasmanita; Widyastuti, Etty (Journal Economics & Business Atmajaya Indonesia, 2018)
This study aims to examine whether the attributes of the quality of accounting information reflect the qualitative characteristics of financial statements and examine the effect of the quality of accounting information on investment efficiency. The attributes of the quality of accounting information are predictability, discretionary revenue, discretionary accruals. Investment efficiency is measured by investment inefficiency as underinvestment and overinvestment. The sample was a manufacturing companies listed on the Indonesia Stock Exchange in 2012 until 2015 as many as 493 observations for examine the attributes of the accounting information quality to form factors that reflect the quality of the financial statements. While the sample of 479 observations used to test the influence of the quality of accounting information against underinvestment. Observation of overinvestment was not analyzed in this study because it has only 14 observations. Data analysis technique used is factor analysis and multiple linear regression. The results showed that the three attributes of the accounting information quality form two factors, the first factor called predictability and the second factor is called discretion. Both of these factors reflect the qualitative characteristics of the accounting information. However, the quality of accounting information measured by these two factors has no significant effect on underinvestment. Likewise, the operating cycle, ROA, and age have no effect on underinvestment. Meanwhile, firm size, tangibility , and dummy loss have a significant effect on underinvestment